Walking in their footsteps: Historical empathy and experiential learning on battlefield study tours - Sara Karn (Historical Encounters: A Journal of Historical Consciousness, Historical Cultures, and History Education, 2024)
Reflecting on my experience leading battlefield study tours for secondary school students, this article explores the pedagogical benefits of experiential learning for fostering historical empathy. I suggest that experiential learning offers students opportunities to engage with both the cognitive and affective dimensions of history, which are necessary for developing historical empathy. In doing so, I adopt Davison’s (2017) conceptualization of historical empathy as a cognitive-affective “pathway” to demonstrate how experiential learning supports students’ understandings of perspectives and experiences in the past. On the study tours, students entered the past by developing emotional connections to historical actors and particular places, based on their family histories and backgrounds. While visiting historic sites and interpreting battlefield landscapes, students worked with the historical record to build contextual knowledge and consider diverse perspectives. Finally, students exited the past to form ethical judgments about the World Wars and applied their learning within their communities back home in Canada.